Sovereignty, Statehood and State Responsibility Essays in Honour of James Crawford - Chinkin, Christine; Baetens, Freya (Cambridge University Press, 2015)
This collection of essays focusses on the following concepts: sovereignty (the unique, intangible and yet essential characteristic of states), statehood (what it means to be a state, and the process of acquiring or losing statehood) and state responsibility (the legal component of what being a state entails). The unifying theme is that they have always been and will in the future continue to form a crucial part of the foundations of public international law. While many publications focus on new actors in international law such as international organisations, individuals, companies, NGOs and even humanity as a whole, this book offers a timely, thought-provoking and innovative reappraisal of the core actors on the international stage: states. It includes reflections on the interactions between states and non-state actors and on how increasing participation by and recognition of the latter within international law has impacted upon the role and attributes of statehood
Title from publisher's bibliographic system (viewed on 12 Feb 2016)
Keywords: Internationales Recht; Sovereignty; State, The; Government liability; International law; Staat; Völkerrecht; Souveränität; Staatshaftung; Aufsatzsammlung; Festschrift